Sho-Based Kampo Medicine Combined With Assisted Reproductive Technology Is Effective for Refractory Infertility and Early Recurrent Miscarriage: A Case Report - Yoshida-Komiya, Hiromi; Ami, Masafumi; Suganuma, Ryota; Mitsuma, Tadamichi (Frontiers in Nutrition, 2021)
Assisted reproductive technology (ART) is an effective treatment developed for infertile couples in the world. As a result, women suffering from infertility benefit from ART treatment. However, even when ART treatment is successfully performed, there are cases where conception is not achieved or maintained. Kampo medicine was originally developed in Japan, and Sho is the central part of Kampo concept. Although it is thought that Kampo medicine is useful for various women-specific symptoms in modern Japan, evidence is still lacking regarding the effectiveness of combination of Sho-based Kampo and Western medicine such as ART. In this article, we report a case of a patient with refractory infertility and early recurrent miscarriage (ERM) of unknown cause who successfully became pregnant with combination therapy of Kampo based on Sho and ART. The patient was a 34-year-old Japanese woman and had been treated with ART in a nearby clinic. In a 3-year period, she had undergone oocyte retrieval twice, frozen embryo transfer (FET) seven times and conceived twice. Since both conceptions ended in miscarriages and pregnancy could not be established thereafter, her clinic referred her to our hospital for Kampo treatment. As result of the diagnosis of her Sho-pattern, we chose Kampo medicine. Finally, she succeeded in conception 1.5 years after beginning treatment and was able to carry the fetus to term successfully. The current case showed that Kampo medicine chosen by the Sho-patterns is useful for refractory infertility and ERM. It is important to note that examinations for evaluting the Sho-patterns are essential for selecting appropriate Kampo medicine. Sho-based Kampo leads to an increase in the effectiveness of ART treatment, and accumulation of evidence that clarifies Sho-pattern is required.